DESIGNING & PILOTING ONLINE TESTS AS PART OF A TEACHER COMPETENCE ASSESSMENT - Butkēviča, Anete; Dudareva, Inese; Namsone, Dace; Čakāne, Līga; Zandbergs, Uldis; Bērtule, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Approaches for competence assessment are becoming increasingly important to plan school development goals, especially during complex educational changes. This paper outlines authors’ experience and recommendations from the designing and piloting of teacher online tests as part of a wider competence management process. A developed theoretical model of a universal teacher competence profile is presented. Tests represent four thematic parts related to teacher performance in classroom to facilitate: student cognitive activation, student self-regulation, student collaboration, and leveraging digital. Test questions were developed based on a framework of teacher performance assessment that consists of a structured set of performance level descriptors to help determine teacher level of competence (0-4) according to criteria developed. Online tests were completed by 197 teachers. Test results were analysed to determine their validity. Proposed online tests can be used for interpreting assessment results of teacher knowledge and beliefs necessary for teaching 21st century skills and plan teacher professional development for goal attainment in schools.